Finding "meaning" in psychology: a lay theories approach to self-regulation, social perception, and social development - Molden, Daniel C; Dweck, Carol S (The American psychologist, 2006)
Much of psychology focuses on universal principles of thought and action. Although an extremely productive pursuit, this approach, by describing only the "average person," risks describing no one in particular. This article discusses an alternate approach that complements interests in universal principles with analyses of the unique psychological meaning that individuals find in their experiences and interactions. Rooted in research on social cognition, this approach examines how people's lay theories about the stability or malleability of human attributes alter the meaning they give to basic psychological processes such as self-regulation and social perception. Following a review of research on this lay theories perspective in the field of social psychology, the implications of analyzing psychological meaning for other fields such as developmental, cultural, and personality psychology are discussed.